Fano Resonances Can Provide Two Criteria to Distinguish Majorana Bound States from Other Candidates in Experiments. (May 2016) - Xiong 熊, Ye 烨
Abstract : There are still debates on whether the observed zero energy peak in the experiment by Stevan et al. [Science 346 (2014) 602] reveals the existence of the long pursued Majorana bound states (MBSs). We propose that, by mounting two scanning tunneling microscopic tips on top of the topological superconducting chain and measuring the transmission spectrum between these two metallic tips, there are two kinds of characteristics on the spectrum that are caused by MBSs uniquely. One is symmetric peaks with respect to zero energy and the other is 4π period caused by a nearby Josephson junction. The former refers to the fact that MBSs are composited by Majorana fermions which distributed in the particle and hole subspaces equally. The latter is based on the well known 4π period of Josephson effect in topological superconductor. We think that such two characteristics can be used as criteria to distinguish MBSs from other candidates, such as impurities, Kondo effect and traditional Andreev bound states.